PEDAGOGICAL MONITORING AND ASSESSMENT SYSTEM IN LANDSCAPE DRAWING LESSONS - Amonova Durdona Aliek qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article examines the pedagogical monitoring and assessment system in landscape drawing lessons. The study focuses on strategies for evaluating students’ technical skills, visual thinking, creativity, and aesthetic perception. Various assessment methods, including formative and summative evaluation, peer review, and self-assessment, are discussed as effective tools for guiding student learning, providing constructive feedback, and improving the overall quality of instruction. The article highlights the importance of systematic assessment in motivating students, tracking progress, and ensuring the development of both artistic competence and cognitive abilities in the landscape drawing process.